QAnon: A False Prophets Conspiracy - Solc, Vladislav (Global Journal of Cultural Studies, 2024)
Examining the QAnon movement through a Jungian lens, this analysis draws parallels between archetypal defense mechanisms and the Homeric myth of Odysseus, specifically his stay on Ogygia Island. The paper introduces terms like "Dark Religion" and "theocalypse," exploring the phenomenon of mind possession in religious fundamentalism and conspiracy theories. Symbolically, Calypso, as "the concealer," functions as an archetypal protective system, diverting ego-consciousness from reality and constructing a false belief system. "Theocalypse" describes religious inflation by unconscious contents, resulting in specific mytho-poetic ideologies and archetypal images whose function is to protect ego from experiencing painful emotions. The manifestation of Dark Religion is evident in QAnon Conspiracy Theory followers who believe in a secret war led by Donald Trump against a satanic child-trafficking cabal. This dark belief system is characterized by traits such as seeking secret signs and clues, absolutism, rejection of modernity, reactivity, aggression, a paranoid worldview, and the assertion of a special ability to see with their hearts—reading between the lines, to name a few. Commonalities between conspiratorial and fundamentalist thinking emerge from the dynamics of inferior consciousness and subsequent ego inflation, explaining both the archetypal nature of conspiracism and its resistance to rational correction. Conspiratorialists assert additional qualities, such as being chosen to perceive the truth, promoting a superior truth without relative values or "gray" areas (superiority). Their knowledge is held unwaveringly and treated as infallible faith, often invoking sources like idols and refusing to question their authority. Vehement rejection of opposing theories (defensive selectivity) characterizes their mindset, along with a surrender of will to their leaders (submission to authority). Conspiracists actively pursue the goal of converting others (reactivity) and accept responsibility for the state of affairs only in a fantasy world, avoiding self-reflection (projection). Conscious thinking remains free from unconscious influence only when recognizing numinous contents and withdrawing projections from objects. A symbolic perspective, treating conspiracy theories as symbols rather than rational constructs, provides a non-dismissive understanding of strong adherence to such beliefs. Examining QAnon symbolically through the lens of Jungian psychology, while understanding how adherents enact unconscious complexes and cultural complexes, offers more effective ways of understanding their beliefs than what traditional schools provide. Breaking away from restrictive beliefs requires embracing living symbols tethered to reality, facilitating genuine feeling-insight, authentic suffering, and thereby fostering a connection with one's psyche.